ANALISIS HUBUNGAN INVESTMENT OPPORTUNITY SET DENGAN KEBIJAKAN PENDANAAN DAN DEVIDEN - Bosar Hasibuan (Universitas Riau Kepulauan, 2017)
This study aims to examine the association between the investment opportunity set (ios) values as firm growth proxy, size as a control variable and corporate policy decisions, such as financing and dividend policy choice using public firms in indonesia stock exchange. eight proxies IOS are use as firm growth indicator, such as market to book value of asset, market to book value equity, price earning ratio,property, plant and equipment to firm value, capital expenditure to firm value, capital expenditure to book value of total asset, total annual depreciation expense to firm value and variance in total return. the variables were analyzed using common factor analysis. the dependent variables are debt to equity ratio, dividend pay out and dividend yield. The samples used in this research are selected using purposive sampling method. this research uses 51 companies that published its financial statement on december 31 for the year 2006 until year 2011 with non negative earning. regression method was applied. The result indicates that growth firm have significantly lower financing than non growth firms. it means growth firm in indonesia stock exchange using internal fund in its company than non growth firms. the others results show that growth firms paid dividend bigger than non growth firms.